Steering the Private Sector in COVID-19 Diagnostic Test Kit Development in South Korea - Lee, Sora (Frontiers in Public Health, 2020)
Responsive private sector engagement in developing test kits for COVID-19 in South Korea offers a valuable case study in public-private partnership and infectious disease governance. Korean biotech firms promptly developed diagnostic test kits and the nation achieved capacity to test over 20,000 people daily. This was a direct result of the continuous application of lessons learned from the Middle Eastern Respiratory Syndrome (MERS) outbreak in 2015. South Korea had been strengthening the private sectors’ infectious disease governance and response capacity, creating various new constructive pathways towards public-private partnership. Regulatory amendments were made to better liaise with the private sector. Government-led investment had increased in the Research and Development of testing technologies over the past five years. Furthermore, the Korean government had introduced fast-tracking approval, allowing open competition for over 20 domestic bio-tech companies to develop test kits. An overview of test kit governance informs us of the importance of public-private partnership for pandemic threats.